Changes in Subjective Age During COVID-19. (7th August 2020) - Terracciano, Antonio; Stephan, Yannick; Aschwanden, Damaris; Lee, Ji Hyun; Sesker, Amanda A; Strickhouser, Jason E; Luchetti, Martina; Sutin, Angelina R
Abstract: Background and Objectives: To examine the change in subjective age with the emergence of coronavirus disease 2019 (COVID-19). Two competing hypotheses were tested: (a) people felt increasingly older due to the stress generated by the pandemic and (b) people felt increasingly younger due to psychological distancing from older age, a vulnerability to COVID-19. Research Design and Methods: An age- and sex-stratified sample of adults from across the United States (baseline N = 3, 738) was assessed on 3 occasions: before the COVID-19 outbreak in late January/early February and during the outbreak in late March and again in late April. Multilevel modeling analysis examined the change in subjective age and tested potential moderators of individual differences in the trajectory of subjective age. Results: The average trajectory of subjective age followed a concave curve, with a nadir (feeling younger) during the second assessment in late March. Older age, negative expectations about aging, absence of preexisting conditions, and less stress during COVID-19 were associated with feeling younger but did not predict the rate of change. The only significant predictor of change in subjective age was the belief that the "coronavirus is only a threat to older adults": The more individuals agreed with this statement, the more likely it was that they felt increasingly younger at follow-up. Discussion and Implications: Subjective age changed during a global health crisis, with people feeling younger with the emergence of COVID-19. The findings support the hypothesis that subjective age partly reflects a coping process of psychological distancing from older age, the age group most vulnerable to COVID-19.